Analisis Penggunaan Google Form Dalam Pelaksanaan PTS di Masa Pandemi Covid-19 Siswa Kelas V SD Negeri 01 Kebondalem - Asep Ardiyanto; Lian Sheila Marifa; Mei Fita Asri Untari (Jurnal Gentala Pendidikan Dasar, 2021)
The Covid-19 pandemic hit Indonesia in mid-March 2020, so the education system in Indonesia had to change. The learning process that was originally done face-to-face now has to be done online or remotely. From this, teachers must be able to use or utilize media or technology as alternative media in the learning process or assessment process. This study aims to analyze the use of Google Forms in the implementation of PTS during the Covid-19 pandemic as an alternative media for fifth grade students of SD Negeri 01 Kebondalem Pemalang Regency and find out the advantages and disadvantages of using it. The method used in this research is descriptive qualitative research method. The data in this study were obtained using data collection techniques in the form of observation, interviews, questionnaires, and documentation. Based on the research, it can be concluded that the use of Google Form can make it easier for teachers to distribute PTS questions to students and make it easier for teachers to make assessments. The shortcomings in its use are that students have difficulty accessing links caused by the availability of quotas, signal interference which can cause pages to not be opened or errors to occur. Another obstacle is that the cellphones used by students are partly owned by their parents so that teachers find it difficult to determine the time limit for work